Functional analysis of Sox8 and Sox9 during sex determination in the mouse. - Wegner, Michael; et al. (Development, 2004)
Sex determination in mammals directs an initially bipotential gonad to differentiate into either a testis or an ovary. This decision is triggered by the expression of the sex-determining gene Sry, which leads to the activation of male-specific genes including the HMG-box containing gene Sox9. From transgenic studies in mice it is clear that Sox9 is sufficient to induce testis formation. However, there is no direct confirmation for an essential role for Sox9 in testis determination. The studies presented here are the first experimental proof for an essential role for Sox9 in mediating a switch from the ovarian pathway to the testicular pathway. Using conditional gene targeting, we show that homozygous deletion of Sox9 in XY gonads interferes with sex cord development and the activation of the male-specific markers Mis and P450scc, and leads to the expression of the female-specific markers Bmp2 and follistatin. Moreover, using a tissue specific knock-out approach, we show that Sox9 is involved in Sertoli cell differentiation, the activation of Mis and Sox8, and the inactivation of Sry. Finally, double knock-out analyses suggest that Sox8 reinforces Sox9 function in testis differentiation of mice.
UnivIS-Import:2015-03-09:Pub.2004.med.IB.LPCIPDBI.functi
Keywords: Conditional gene targeting; Gonads; Mouse; Sex determination